2006
DOI: 10.1152/ajplung.00173.2005
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin-mediated endocytosis of FITC-albumin in alveolar type II epithelial cell line RLE-6TN

Abstract: -We examined mechanisms of FITC-albumin uptake by alveolar type II epithelial cells using cultured RLE-6TN cells. Alkaline phosphatase activity and the expression of cytokeratin 19 mRNA, which are characteristic features of alveolar type II epithelial cells, were detected in RLE-6TN cells. The uptake of FITCalbumin by the cells was time and temperature dependent and showed the saturation kinetics of high-and low-affinity transport systems. FITC-albumin uptake was inhibited by native albumin, by chemically modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 43 publications
7
89
0
Order By: Relevance
“…The concentrations of both inhibitors employed were effective at inhibiting the uptake of FITC-albumin in type II and type I-like cells as well as in RLE-6TN cells. 10,14) In addition, potassium depletion exhibited only a slight decrease in FITC-insulin uptake in both cells (Fig. 3C).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The concentrations of both inhibitors employed were effective at inhibiting the uptake of FITC-albumin in type II and type I-like cells as well as in RLE-6TN cells. 10,14) In addition, potassium depletion exhibited only a slight decrease in FITC-insulin uptake in both cells (Fig. 3C).…”
Section: Discussionmentioning
confidence: 88%
“…We previously characterized FITC-albumin uptake in rat primary cultured alveolar type II and type I-like epithelial cells as well as in RLE-6TN cells, an established cell line having some characteristics of type II cells. 10,14,15) In this study, the characteristics of FITC-insulin uptake were further examined.…”
Section: Discussionmentioning
confidence: 99%
“…PAO is a widely used inhibitor of clathrin-mediated endocytosis (28,29) that completely blocks the endocytosis of GABA B Rs (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…It has now been demonstrated that, similarly to that of in the kidney proximal tubule, excess intra-alveolar albumin can be taken up by the alveolar epithelial cells by a clathrin-mediated endocytic process after albumin bound to the multiligand receptor megalin (21,265,266). The system appears to have the necessary capacity to remove large amounts of alveolar albumin (21), highlighting its potential relevance in alveolar epithelial fluid balance in ALI.…”
Section: L669 Acute Lung Injury and Barrier Dysfunctionmentioning
confidence: 99%